2013
DOI: 10.4103/0970-0358.118606
|View full text |Cite
|
Sign up to set email alerts
|

Phalloplasty: The dream and the reality

Abstract: Phalloplasty has come a long way as Plastic Surgery has evolved over the years. The complication ridden multistage tube pedicles popularized by Gillis were, with the advent of microsurgery, replaced by radial forearm flaps. The composite osteo-cutaneous version of this flap promised ‘All for one and one for all’ assuring both a reliable urinary conduit and a phallus stiffener. Prelamination and prefabrication to make the neo-urethra came with the promise of reducing both fistula and strictures but that did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…Oophorectomy: surgical removal of one or both ovaries Orchiectomy: surgical removal of one or both testicles Ovariectomy: surgical removal of one or both ovaries Parenteral administration: intravenous injection (into a vein) or intramuscular infusion (into muscle) of medication Penectomy: surgical removal of the penis Phalloplasty: surgical creation/reconstruction of a penis using one of a variety of techniques including free or pedicled (attached) flap (see Rashid and Tamimy, 2013) Primary sex characteristics: physical characteristics/sex organs directly involved in reproduction Salpingo-oophorectomy: removal of the ovaries and fallopian tubes Scrotoplasty: surgical creation/reconstruction of testicles; in transmen, native labia tissue is used; testicular implants can be used Secondary sex characteristics: physical characteristics that appear at puberty and vary by sex but are not directly involved in reproduction (e.g., breasts) Sex: a person's biological status as male or female based on chromosomes, gonads, hormones, and genitals (intersex is a rare exception)…”
Section: -2 Inchesmentioning
confidence: 99%
“…Oophorectomy: surgical removal of one or both ovaries Orchiectomy: surgical removal of one or both testicles Ovariectomy: surgical removal of one or both ovaries Parenteral administration: intravenous injection (into a vein) or intramuscular infusion (into muscle) of medication Penectomy: surgical removal of the penis Phalloplasty: surgical creation/reconstruction of a penis using one of a variety of techniques including free or pedicled (attached) flap (see Rashid and Tamimy, 2013) Primary sex characteristics: physical characteristics/sex organs directly involved in reproduction Salpingo-oophorectomy: removal of the ovaries and fallopian tubes Scrotoplasty: surgical creation/reconstruction of testicles; in transmen, native labia tissue is used; testicular implants can be used Secondary sex characteristics: physical characteristics that appear at puberty and vary by sex but are not directly involved in reproduction (e.g., breasts) Sex: a person's biological status as male or female based on chromosomes, gonads, hormones, and genitals (intersex is a rare exception)…”
Section: -2 Inchesmentioning
confidence: 99%
“…The lateral sural cutaneous nerve allowed for the retention of sensation. The superficial peroneal nerve provided the sensation for donors of the lower extremity (Rashid and Tamimy, ). The results demonstrated that although patients in both categories successfully achieved an erection, only about fifty percent of patients reported sensation in the neophallus.…”
Section: Evolution Of Female‐to‐male Transgender Genital Reconstructionmentioning
confidence: 99%
“…Random pattern flaps, pedicled flaps (groin flap, anterolateral thigh flap, island tensor fascia lata flap), free flaps (radial forearm free flap, osteocutaneous radial forearm free flap, lateral arm free flap, osteocutaneous free fibula, anterolateral thigh free flap, latissimus dorsi free flap, free scapular flap) would be used for phalloplasty operations (Figure 3). [9] Neophallus should provide a satisfying and aesthetitc appearance and also neourethra should allow comfortable voiding while standing. [1,9,10] In addition, tactile and erogeneous sensibility, enough bulk for a stiffener insertion are also important features.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Neophallus should provide a satisfying and aesthetitc appearance and also neourethra should allow comfortable voiding while standing. [1,9,10] In addition, tactile and erogeneous sensibility, enough bulk for a stiffener insertion are also important features. [1,9,10] This study was designed for reviewing the literature for phalloplasty articles and comparing the results and complications of this surgery.…”
Section: Introductionmentioning
confidence: 99%